Familial mediterranean fever mutation analysis in pediatric patients with İnflammatory Bowel Disease: A multicenter study - Urganci, Nafiye; Ozgenc, Funda; Kulo?lu, Zarife; Yüksekkaya, Hasan; Sari, Sinan; Erkan, Tülay; Yaman, Aytaç (AVES, 2021)
Background: The aim of the study was to evaluate familial Mediterranean fever (FMF) mutation analysis in pediatric patients with inflammatory bowel disease (IBD). The relation between MEFV mutations and chronic inflammatory diseases has been reported previously. Methods: Children with IBD (334 ulcerative colitis (UC), 224 Crohn's disease (CD), 39 indeterminate colitis (IC)) were tested for FMF mutations in this multicenter study. The distribution of mutations according to disease type, histopathological findings, and disease activity indexes was determined. Results: A total of 597 children (mean age: 10.8 ± 4.6 years, M/F: 1.05) with IBD were included in the study. In this study, 41.9% of the patients had FMF mutations. E148Q was the most common mutation in UC and CD, and M694V in IC (30.5%, 34.5%, 47.1%, respectively). There was a significant difference in terms of endoscopic and histopathological findings according to mutation types (homozygous/ heterozygous) in patients with UC (P < .05). There was a statistically significant difference between colonoscopy findings in patients with or without mutations (P = .031, P = .045, respectively). The patients with UC who had mutations had lower Pediatric Ulcerative Colitis Activity Index (PUCAI) scores than the patients without mutations (P = .007). Conclusion: Although FMF mutations are unrelated to CD patients, but observed in UC patients with low PUCAI scores, it was established that mutations do not have a high impact on inflammatory response and clinical outcome of the disease. Copyright © 2021 by The Turkish Society of Gastroenterology.
Keywords: Children; Familial mediterranean fever; Inflammatory bowel disease; MEFV; Mutation analysis